On the Origin of Cattle: How Aurochs Became Cattle and Colonized the World - Ajmone-Marsan, Paolo; Garcia, José Fernando [UNESP]; Lenstra, Johannes A. (Wiley-Blackwell, 2010)
Since their domestication in the Neolithic, cattle have belonged to our cultural heritage. The reconstruction of their history is an active field of research 1 that contributes to our understanding of human history. Archeological data are now supplemented by analyses of modern and ancient samples of cattle with DNA markers of maternal, paternal, or autosomal inheritance. The most recent genetic data suggest that maternal lineages of taurine cattle originated in the Fertile Crescent with a possible contribution of South-European wild cattle populations, while zebu cattle originate from the Indus Valley. Subsequently, cattle accompanied human migrations, which led to the dispersal of domestic cattle of taurine, indicine, or mixed origin over Asia, Africa, Europe, and the New World. This has resulted in their adaptation to different environments and considerable variation in appearance and performance. More recently, rational management of breeding led to international movements of sires, which again changed the global patterns of genetic diversity.
Keywords: domestication; Bos indicus; Bos taurus; mtDNA; Y-chromosome